The Impostor Phenomenon: Toward a Better Understanding of the Nomological Network and Gender Differences - Fleischhauer, Monika; Wossidlo, Josephine; Michael, Lars; Enge, Sören (Frontiers in Psychology, 2021)
The impostor phenomenon (IP) refers to the tendency to perceive oneself as intellectually incompetent and to attribute one's own success to effort-related or external factors such as fortunate circumstances. The present study (N = 209) aimed to contribute to open questions regarding gender differences in the IP and the nomological network of the IP. The results show that the consistently found key correlates of the IP, i.e. lower self-esteem and higher neuroticism, could also play a role in explaining why women report higher impostor feelings than men in many studies. Moreover, the results suggest that IP is characterized by the more maladaptive, socially prescribed perfectionism, which is related to the belief that others expect perfection from oneself, whereas self-oriented perfectionism, which is characterized by a critical view on oneself, plays a smaller role in differences in the IP. Finally, a strong association with the sandbagging construct challenges the conceptualization of the IP as a genuine doubt about one's own competence, because similarly to IP, sandbaggers present themselves negatively to others, but do so for very strategic reasons in order to create a low expectation base in other individuals. Regression analysis was used to assess the incremental value of the personality factors in explaining variance in the IP. It was found that sandbagging and IP are highly related but not interchangeable.